PROSPECTS OF DEVELOPMENT OF PROCESSES OF OIL REFINING AND ON OIL-EXTRACTING ENTERPRISES IN NIGERIA - Бабатунде, О. О.; Бойченко, С. В.; Черняк, Л. М. (Science-based technologies, 2016)
Nigeria's reserves in 22 mlrd.barr. oil and production in volume 2 mln.b/d oil industry is the foundation of the Nigerian economy. Nigerian oil is high quality. Production is mainly in swampy areas of the Niger Delta, and on the continental shelf. In recent years, mining companies focus on oil in the sea. Nigeria produces several varieties of high-quality oil. The main of them «Eskravos», «Forçados River», «Odude» and «Bonnie». The latter is collectively called Nigerian oil price on the world market by 10-15 cents higher than the price of North Sea «Brent». For a number of reasons, including aging and failure of equipment, refineries are part-power. Thus, one of the key processes of oil will analyze modular construction of private refineries (refinery) 65 companies. The basis of this refinery is a mobile unit. Each module carries a part of the refining process unit, which are interconnected by intermediate pipes that form easily controlled production.